Esquistossomose: reprodução e expansão da endemia no Estado de Pernambuco no Brasil Schistosomiasis: reproduction and expansion of the endemic region in Brazil - Constança Simões Barbosa; Carlos Bernardo da Silva; Frederico Simões Barbosa (Universidade de São Paulo, 1996)
A esquistossomose continua a ser um problema de saúde pública no Nordeste do Brasil embora o emprego, em larga escala, da quimioterapia venha sendo apontado como um dos fatores responsáveis pela redução das formas graves. O Estado de Pernambuco vem apresentando taxas crescentes de infecção humana para esquistossomose com perfil epidemiológico de prevalências crônicas (até 80%) na região rural e casos recentes de infecção aguda no litoral. Discute-se a reprodução e expansão da esquistossomose a partir de uma concepção estrutural e histórica de causas, onde se inserem fatores não só de ordem biológica mas também sociais, políticos e culturais que vêm contribuindo para a formação dos quadros endêmicos: a forma de ocupação e do uso da terra, desemprego, desnutrição, migração e outros. Questionam-se as crescentes dificuldades para o controle da doença e o papel da investigação epidemiológica na compreensão da essência social do processo saúde/doença. Schistosomiasis mansoni can be considered an important public health problem in Northeastern Brazil, in spite of the reduction in the prevalence of the hepatosplenic clinical forms which have been attributed to the large scale use of chemotherapy in this country. However, the rise in the prevalence rates and the spread of this endemic disease to new areas show that schistosomiasis is assuming its must cruel expression: less lethal but more greatly incapacitating in terms of irreversible physical and moral damage to human beings. The state of Pernambuco presents growing rates for schistosomiasis infection in humans. The epidemiological profile of this disease displays high and consistent prevalence rates (up to 80%) in rural areas, and new cases of acute infection on the coast, where schistosomiasis has recently been introduced. The reproduction and expansion of this endemic disease can be better understood on the basic of a conception of structural and historical causation. The disease construction process should be reconstructed in the light of biological as well as the social, political and cultural factors which are jointly responsible for the present endemic situation. Within that frame work, the historical and socio-economic features that interact with the parasite and give rise to the present proportions of the schistosomiasis epidemic in Pernambuco are discussed. The mode of occupation and use of the land, unemployment, under-nutrition, migration, etc., raise the question of the growing difficulties confronting the control of the disease, both in rural areas where populations are extremely mobile as well as in the poorly organized urban population. Epidemiological investigation is fulfithing its role in its attenpts to understand the complex relationships of an intrinsecally social nature of the health/disease process between health problems and the quality of life for the purpose of producing consistent disease control models.